Genome-Wide Analysis of DREB Genes Identifies a Novel Salt Tolerance Gene in Wild Soybean (Glycine soja) - Hou, Zhihong; Li, Yongli; Cheng, Yuhan; Li, Weiwei; Li, Tai; Du, Hao; Kong, Fanjiang; Dong, Lidong; Zheng, Dianfeng; Feng, Naijie; Liu, Baohui; Cheng, Qun (Frontiers in Plant Science, 2022)
Salt stress is a major factor limiting the growth and yield of soybean (Glycine max). Wild soybeans (Glycine soja) contain high allelic diversity and beneficial alleles that can be re-introduced into domesticated soybeans to improve adaption to the environment. However, very few beneficial alleles have been identified from wild soybean. Here, we demonstrate that wild soybean is more salt tolerant than cultivated soybean and examine dehydration responsive element-binding (DREB) family transcription factor genes to look for advantageous alleles that might improve drought tolerance in cultivated soybean. Our genome-wide analysis identified 103 DREB genes from the Glycine max genome. By combined RNA-sequencing and population genetics of wild, landrace, and cultivated soybean accessions, we show that the natural variation in DREB3a and DREB3b is related to differences in salt tolerance in soybean accessions. Interestingly, DREB3b, but not DREB3a, appears to have undergone artificial selection. Soybean plants carrying the wild soybean DREB3b allele (DREB3b39Del) are more salt tolerant than those containing the reference genome allele (DREB3bRef). Together, our results suggest that the loss of the DREB3b39Del allele through domestication of cultivated soybean may be associated with a reduction in salt tolerance. Our findings provide crucial information for improving salt tolerance in soybean through molecular breeding.